MODIFIKASI MESIN PEMOTONG RUMPUT MENJADI MESIN TRACTOR PORTABLE - Indra Lesmana; Fadelan Fadelan; Yoyok Winardi (Universitas Muhammadiyah Ponorogo, 2022)
Indonesia is a potential area for producing food such as rice, fruit and vegetables. However, in the process of processing land, the community still uses manual methods so that it takes a long time. This study aims to increase the efficiency and effectiveness of farmers in cultivating land so that farmers can maximize their work. This research resulted in a portable tractor that can be used to cultivate land in loose soil which is usually the land that is often chosen by farmers to grow various kinds of vegetables. This portable tractor uses a 2 stroke lawn mower, blades and a frame made of 20 mm iron pipe. Researchers have tested portable tractors in the field. From the testing process, it shows that the portable tractor machine is able to cultivate 19.5 m2 of loose soil with a depth of 10 cm within 1 hour of testing, so it can be concluded that the use of portable tractors is more effective and efficient than manual land cultivation.